2022
DOI: 10.1177/2325967121s00494
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Adolescent Displaced Clavicle Fractures: A Facts Study

Abstract: Background: The phenomenon of bony remodeling of healed displaced clavicle midshaft fractures in adolescents remains poorly understood. Hypothesis/Purpose: The purpose of the current study was to evaluate and quantify clavicle remodeling in a large population of adolescents with completely displaced fractures treated non-operatively to understand the factors that may influence this process. Methods: Patients were identified from the database(s) of a multi-center study group investigating the functional outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Representative cases demonstrating the remodeling capacity of nonsurgically management adolescent diaphyseal clavicle fracture. 10 In this review of 81 patients at a mean follow-up of 3 years, fracture shortening, superior displacement, and angulation markedly improved by 60%, 57%, and 38%, respectively. All patients were younger than 14 years and 83% of patients were 14 years and older at the time of injury with a minimum follow-up of 4 years for complete/near-complete remodeling.…”
Section: Malunionmentioning
confidence: 82%
See 2 more Smart Citations
“…Representative cases demonstrating the remodeling capacity of nonsurgically management adolescent diaphyseal clavicle fracture. 10 In this review of 81 patients at a mean follow-up of 3 years, fracture shortening, superior displacement, and angulation markedly improved by 60%, 57%, and 38%, respectively. All patients were younger than 14 years and 83% of patients were 14 years and older at the time of injury with a minimum follow-up of 4 years for complete/near-complete remodeling.…”
Section: Malunionmentioning
confidence: 82%
“…9 Most recently, the FACTS (Function after Adolescent Clavicle Trauma and Surgery) study group demonstrated that 85% of patients were younger than 14 years and 54% of patients were 14 years or older at the time of injury, with a minimum follow-up of 4 years for complete/near-complete remodeling (Figure 5). 10 This contrasts with adult populations in which completely displaced diaphyseal clavicle fractures demonstrate little propensity for remodeling and carry high nonunion rates with nonsurgical management. 11…”
Section: Unique Considerations In the Skeletally Immature Claviclementioning
confidence: 99%
See 1 more Smart Citation
“…Bone remodeling was evaluated as either complete/near complete, moderate, or incomplete, as previously described (Figure 1). 24 Radiographic measurements were performed on the initial AP view of the affected clavicle, taken at the time of injury, and on the follow-up image. These measurements included end-to-end fracture shortening (in millimeters), superior fracture displacement (in millimeters), and fracture angulation (in degrees).…”
Section: Methodsmentioning
confidence: 99%
“…The American Journal of Sports Medicine 2024;52(4):1032-1039 DOI: 10.1177/03635465241228818 Ó 2024 The Author(s) from the initial investigation of McGraw et al 14 to more recent imaging studies 11,24 ; and (3) an increased body of research performed within the past decade assessing outcomes of various management strategies specific to adolescent clavicular fractures. 1,8,13,23,28,32 This prospective study aimed to assess longer-term outcomes of nonoperatively treated teenagers with completely displaced midshaft clavicular fractures.…”
Section: -In-5mentioning
confidence: 99%